1979
DOI: 10.1007/bf02293790
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficiency and effectiveness of interactively selected MDS data designs

Abstract: multidimensional scaling, INTERSCAL, incomplete data designs,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…The rms error remains below 9 mm for , even when nearly 40% of the measurements are unavailable, and also below 9 mm for , even when nearly 80% of the measurements are unavailable. These results confirm the statements of previous researchers that only about 25%-33% of the measurements are needed in practice [4], [5].…”
Section: B Handling Missing Datasupporting
confidence: 95%
See 1 more Smart Citation
“…The rms error remains below 9 mm for , even when nearly 40% of the measurements are unavailable, and also below 9 mm for , even when nearly 80% of the measurements are unavailable. These results confirm the statements of previous researchers that only about 25%-33% of the measurements are needed in practice [4], [5].…”
Section: B Handling Missing Datasupporting
confidence: 95%
“…The square of the residual distance from to the -axis can be computed from (2) and (3) (4) Rearranging terms yields a convenient formula that we will use again (5) Let us orient the axes so that a third point lies in the -plane (i.e.,…”
Section: B Deriving a 2-d Basismentioning
confidence: 99%
“…However, the selection of the pairs before data collection results in little to no information on subsets of brands, respondents, and the relation between these two. The subset of brands can also be determined interactively during the judgment task [20]. However, such procedures are deterministic in nature, and the selection of which brands to be compared is based on technical details of the estimation procedure and not on brand or consumer factors that affect the quality of the judgments.…”
Section: The Scaling Of Large Brand Setsmentioning
confidence: 99%
“…Monte carlo evaluation (Baker & Young, 1978;Girard & Cliff, 1976;Hamer, 1978) has shown that when the Euclidean assumption is satisfied, ISIS performs well using only 25Te to 45% of the possible pairs and is generally superior to fixed designs with the same fraction of data. On the basis of monte carlo, and other work, an improved program called INTERS CAL has been developed (Cliff, Girard, Green, Kehoe, & I~®herty, 1977;Green & Bentler, 1979) and should probably be preferred to the earlier versions of ISIS. Of course, when the data do not satisfy the Euclidean assumption, it may be desirable to consider fixed designs or a procedure like ISO, which is discussed below.…”
Section: Incomplete Design Studiesmentioning
confidence: 99%